La productividad laboral y su relación con el clima laboral de los trabajadores de las medianas empresas en el sector lácteo. - Díaz Jimenez, Jessica Estefania (2024)
The research focused on the relationship between labor productivity and work environment in medium-sized companies in dairy sector in Cotopaxi province. A quantitative approach and a descriptive/relational design were used. To collect data, the survey was used and two questionnaires were applied: the first one, intended to evaluate working environment, addresses 5 dimensions (self-realization, work involvement, supervision, communication and working conditions); the second one, focused on measuring productivity level , it evaluates 3 dimensions (human talent, machinery, equipment, materials and work organization). The results revealed that the most of companies have a working environment classified as regular (60%) and work productivity at a normal level (61.7%). Significant positive relationships were found between work involvement and human talent, as well as with work organization in specific companies such as Tanilact Cotopaxi and La Avelina. In Tanilact Cotopaxi, a significant relationship between self-actualization and work organization was also highlighted. In conclusion, workers in medium-sized dairy companies in Cotopaxi predominantly experience a regular work environment and normal work productivity. The research highlights direct importance of working environment,and productivity. These findings contribute to the understanding of how the working environment influences productivity, highlighting key areas for improvement and effective management in the dairy sector.